2006
DOI: 10.1029/2005jc002964
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional ageostrophic secondary circulation at ocean fronts due to vertical mixing and large‐scale deformation

Abstract: [1] Ageostrophic secondary circulation (ASC) in frontal data sets have been previously diagnosed using only adiabatic versions of Omega equations. This study includes the effect of vertical mixing on such diagnostics. Modified quasi-geostrophic and semigeostrophic balance equations are examined for the existing Azores front data sets and idealized fronts in the presence of diabatic vertical mixing as well as a large-scale deformation field. The relevant dimensionless parameter representing the relative importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 43 publications
4
93
0
Order By: Relevance
“…They used realistic and idealized numerical model calculations, along with an analytic theory, to describe the frontogenesis resulting from spatial variability in turbulent mixing, a process they call turbulent thermal wind (TTW). This drives frontogenesis and downwelling in the vicinity of dense filaments as is found here, a phenomenon that has also been derived in two-dimensional theoretical calculations (e.g., Garrett and Loder 1981;Thompson 2000;Nagai et al 2006).…”
Section: Dynamics and Water Mass Transformationmentioning
confidence: 60%
“…They used realistic and idealized numerical model calculations, along with an analytic theory, to describe the frontogenesis resulting from spatial variability in turbulent mixing, a process they call turbulent thermal wind (TTW). This drives frontogenesis and downwelling in the vicinity of dense filaments as is found here, a phenomenon that has also been derived in two-dimensional theoretical calculations (e.g., Garrett and Loder 1981;Thompson 2000;Nagai et al 2006).…”
Section: Dynamics and Water Mass Transformationmentioning
confidence: 60%
“…Other processes-such as wind-induced frictional forces, diabatic processes, time-dependent near-and super-inertial motions, or higher-order corrections to the quasigeostrophic omega equation-could also generate vertical motion (Viú dez et al 1996;Giordani et al 2006;Nagai et al 2006;Thomas et al 2010). For example, a spatially uniform wind blowing over a current with lateral variations in vertical vorticity will generate Ekman pumping/suction owing to the modification of the Ekman transport by the vorticity (Stern 1965;Niiler 1969).…”
Section: February 2010 N O T E S a N D C O R R E S P O N D E N C Ementioning
confidence: 99%
“…[11] Enhanced departures from geostrophic shear (Figure 4c Nagai et al, 2006] illustrate that the along frontal ageostrophic shear can be forced by the internal geostrophic stress, i.e.,…”
Section: Source Of the Turbulencementioning
confidence: 99%
“…Several studies have found that turbulent mixing [Garrett and Loder, 1981;Thompson, 2000;Nagai et al, 2006Nagai et al, , 2008 and the alongfront component of the wind forcing [Thomas, 2005;A. Mahadevan et al, Rapid changes in mixed layer stratification driven by submesoscale instabilities and winds, submitted to Journal of Geophysical Research, 2009] also provide generation mechanisms for the ASCs. Furthermore, recent theoretical studies using high-resolution numerical models have illustrated that surface trapped forward energy cascade due to turbulent mixing near fronts, associated with unbalanced submesoscale flows, provides a direct route for kinetic and potential energy to be dissipated, [Capet et al, 2008;McWilliams, 2008; M. J. Molemaker et al, Balanced and unbalanced routes to dissipation in an equilibrated Eady flow, submitted to Journal of Fluid Mechanics, 2009] addressing the conundrum of how energy goes from larger to smaller scales.…”
Section: Introductionmentioning
confidence: 99%